Effect of Herbal and Fluoride Mouth Rinses on Streptococcus mutans and Dental Caries among 12–15-Year-Old School Children: A Randomized Controlled Trial - Vinej Somaraj; Rekha P. Shenoy; Ganesh Shenoy Panchmal; Vijaya Kumar; Praveen S. Jodalli; Laxminarayan Sonde (International Journal of Dentistry)
To assess and compare the effect of herbal and fluoride mouth rinses on Streptococcus mutans count and glucan synthesis by Streptococcus mutans and dental caries, a parallel group placebo controlled randomized trial was conducted among 240 schoolchildren (12–15 years old). Participants were randomly divided and allocated into Group I (0.2% fluoride group), Group II (herbal group), and Group III (placebo group). All received 10 ml of respective mouth rinses every fortnight for a period of one year. Intergroup and intragroup comparison were done for Streptococcus mutans count and glucan synthesis by Streptococcus mutans and dental caries. Streptococcus mutans count showed a statistically significant difference between Group I and Group III (p=0.035) and also between Group II and Group III (p=0.039). Glucan concentration levels showed a statistically significant difference (p=0.024) between Group II and Group III at 12th month. Mean DMF scores showed no statistical difference between the three groups (p=0.139). No difference in the level of significance was seen in the intention-to-treat and per-protocol analysis. The present study showed that both herbal and fluoride mouth rinses, when used fortnightly, were equally effective and could be recommended for use in school-based health education program to control dental caries. Trial registration number is CTRI/2015/08/006070.